Diagnostic Valuation of Serum miR-184 and miR-191 in Patients With Non-Small-Cell Lung Cancer. (22nd October 2020) - Ding, Hao; Wen, Wei; Ding, Qingqing; Zhao, Xin
Objective: This study aims to determine the diagnosis and prediction value of serum miR-184 and miR-191 levels in patients with non-small-cell lung cancer (NSCLC). Methods: One hundred patients with NSCLC were enrolled (NSCLC group) and treated with gefitinib. In addition, 59 pneumonia cases (pneumonia group) and 51 healthy cases in the corresponding period (normal group) were included. Serum miR-184 and miR-191 expressions were detected by real-time quantitative polymerase chain reaction. Furthermore, the relationships between serum miR-184 and miR-191 expressions and clinicopathological parameters were analyzed. The use of serum miR-184 and miR-191 levels in the diagnosis of NSCLC and the prediction of treatment effectiveness and 3-year overall survival (OS) were assessed by the receiver operating characteristic curve. Hazard factors affecting the efficacy of treatment in patients with NSCLC were determined by logistic regression. Results: The serum levels of miR-184 in the NSCLC group were significantly lower than those in the pneumonia group and normal group, whereas miR-191 expression was significantly higher in the NSCLC group. Serum miR-184 and miR-191 levels were closely correlated with smoking history, the tumor node metastasis (TNM) stage, and the degree of pathological differentiation. The area under curve (AUC) of serum miR-184 combined with miR-191 in the diagnosis of patients in the NSCLC group and normal group, NSCLC group and pneumonia group, and the efficacy of treatment in patients with NSCLC was 0.925, 0.929, and 0.916, respectively. The AUC of serum miR-184 and miR-191 for the 3-year OS in patients with NSCLC was 0.869 and 0.879, respectively. Smoking history, the degree of pathological differentiation, local treatment, miR-184, and miR-191 were independent risk factors that affected treatment efficacy. Conclusion: Serum miR-184 and miR-191 levels can potentially be used as molecular markers to diagnose and predict the curative effect of treatment in patients with NSCLC.